1998
DOI: 10.1046/j.1365-2583.1998.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and associated mutational effects of the cysteine proteinase (CP1) gene of Drosophila melanogaster

Abstract: The complete structure of the cysteine proteinase (CP1) gene reveals two large 5' introns as well as a small third intron. Deletion studies have shown that null mutations for the locus are female sterile with partial male sterility as well as wing and pigmentation effects. Null alleles can be produced by either deletions to the left or deletions to the right of a P element insertion in the long second intron of the gene. A nearby phenylalanyl tRNA synthetase gene (Pts) was also identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…In some cases NHEJ was inferred from a PCR fragment larger or smaller than that expected from templated repair. In other cases, the mutant phenotype of the CP1 gene (Gray et al 1998) implied loss of sequences flanking the insertion, as would be consistent with end joining. For example, the 4-kb deletion yielded 91 offspring of category A9 (Table 1).…”
Section: Discussionmentioning
confidence: 64%
“…In some cases NHEJ was inferred from a PCR fragment larger or smaller than that expected from templated repair. In other cases, the mutant phenotype of the CP1 gene (Gray et al 1998) implied loss of sequences flanking the insertion, as would be consistent with end joining. For example, the 4-kb deletion yielded 91 offspring of category A9 (Table 1).…”
Section: Discussionmentioning
confidence: 64%
“…b encodes a product involved in b-alanine biosynthesis; b mutants are heavily pigmented. Cp1 encodes a product with cathepsin L activity; deletion studies of Cp1 have shown complete female sterility and reduced pigmentation in abdominal segments 1-5 (Gray et al 1998). Bc encodes a tyrosinase, which catalyzes the de novo synthesis of melanin from tyrosine (Wittkopp et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The first introns of the cow and dog orthologs also are located 11 nucleotides upstream of the ATG initiation codon [59,60]. An intron also is present in the 5 0 -UTR of the Drosophila melanogaster ortholog [61], which is located 13 nucleotides upstream of the translation start site. Since the location of the Ctsl first intron within the 5 0 -UTR is highly conserved in several species, this common feature invites the speculation that the Ctsl first intron plays a general role in the upregulation of this gene.…”
Section: Location Of the Ctsl First Intron Is Conserved In Several Spmentioning
confidence: 99%